Pengembangan Sektor Industri Pada Ekonomi Industri Baru - Iluh Nadila Rahma; Yosse Putra Oentoro; Muhammad Romadhoni Adi Setiawan; Muhammad Yasin (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
The development of the industrial sector in the new industrial economy is an effort made by a person or several people, whether in the form of individuals or organizations, who provide assistance both materially and non-materially with the aim of making something better than before, by processing materials so that they have economic value. High levels are accompanied by intellectual creativity and innovation as wealth that can create money, job opportunities, income and prosperity.